Schizophrenia as a cause for declaring a marriage null - LESZCZYŃSKI, GRZEGORZ (Prawo Kanoniczne, 2017)
Taking up the issue of schizophrenia as a cause for declaring a marriage null and voit, the author begins his reflections with a look at psychosis. From the point of view of marriage validity, of special significance is also the analysis of schizophrenia with very particular medical aspects. The cause of nullity of a marriage discussed here, in turn, requires a rather precise definition of schizophrenia and the factors by which it may be triggered. The last part of the author’s reflections is devoted to the analysis of canon 1095 of the Code of Canon Law, especially to the definition of cases when this schizophrenia is serious enough to exclude marriage validity.